EFFECT OF CEREBRAL VASOSPASM ON DISEASE OUTCOMES IN PATIENTS WITH SEVERE TRAUMATIC BRAIN INJURY - A. Y. Karpunin; S. S. Petrikov; L. T. Khamidova; V. V. Krylov (Неотложная медицинская помощь)
ABSTRACT. Cerebral vasospasm  (CV) is an urgent  issue in the treatment of patients with severe traumatic brain injury (STBI).OBJECTIVES. The aim of this study was to evaluate the effect of cerebral  vasospasm  on outcomes  of STBI.MATERIAL AND METHODS. The study included  43 patients with isolated  and assocoated STBI. The depression of consciousness in patients upon admission  was 8 or less according to the Glasgow Coma Scale (GCS).RESULTS. Cerebral vasospasm  was revealed  in 33 (77%) patients. Groups were comparable according  to age, type of TBI, GCS and average  AP upon admission  to hospital. The analysis of the disease  outcomes according  to GOS revealed  significant  between-group differences  in the  assessment of favorable outсomes (score 4–5, GOS), unfavorable  outcomes  (score 2–3, GOS) and deaths. In patients without CV and with moderate CV, the rate of cases with GOS 1 and GOS 2–3  was 30% (n=3) and 31% (n=5), respectively, and in patients with significant CV it was 82% (n=14).CONCLUSION. The development of significant  cerebral  vasospasm  in patients with severe  traumatic brain injury results in increased mortality by 21% and recovery with adverse neurological  outcomes  by 31%. The post-traumatic CV may cause  secondary  ischemic  brain  damage,  resulting  in considerable disturbance of cerebral  oxygenation.